Strategi Public Relations PC. GKBI dalam Membangun Citra Positif Perusahaan - Nurhaliza, Dina; Andiyansari, Popi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Building an image is a vital endeavor for companies to survive in today's industry competition. This research focuses on the Public Relations strategy of PC. GKBI in creating a positive image. The research objective is to identify the Public Relations strategy of PC. GKBI in the formation of a positive image. The method used is descriptive qualitative, with analysis based on Philip Kotler's Public Relations mix theory, namely the PENCILS strategy. The findings show that PC. GKBI has successfully implemented the PENCILS strategy in building a positive image, although the implementation of Publications and News has not been carried out optimally. It is expected that Public Relations can improve media management so that information dissemination is more massive.